PENGARUH TERAPI AL ZIKIR TERHADAP KUALITASTIDUR LANSIA - Ricer ' Reflio; Ari Pristiana Dewi; Wasisto ' Utomo (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract The elderly is a person who has attained the age of 60 years and over. Sleeping towards dhikr is a therapy for evoke the relaxation response which is expected to improve sleep quality. This study aims to look at the effect of dhikr therapy on the quality of sleep of elderly.This study used a quasi-experiment design with control group. The sampling technique used total sampling and random sampling with 42 respondents which were divided into 21 respondents as intervention group and 21 respondents as control group. Intervention administered for onedays. Evaluation of sleep quality scores using the Pittsburgh Sleep Quality Index (PSQI) questionnaire. Differences sleep quality score of each group tested by dependent t test and differences in sleep quality between the control and intervention groups tested by independent t test.The results of this study indicate there is a strong influence of the dhikr with the quality of the sleep intervention group before and after (p=0,000; α=5%). There is no significant effect mean score meaningful sleep quality in the control group (p= 0,833; α=0,05). There was differences in the mean scores meaningful sleep quality between the intervention group and the control group with p value= 0,000 (<0,05). The power of dhikr has a strong influence on the improvement of the quality of sleep in the intervention group.The result is expected of dhikr therapy to be one nursing intervention to improving sleep quality of elderly. Key words: Dhikr therapy, elderly, quality of sleep References: 41 (2004-2014)